Evaluating usability of mobile application for Dyslexia disability - Muhamad, Suhazli (2018)
In millennium era, Information and Computer Technology becomes very crucial in everyday life. User able to perform various tasks such as education, entertainment, business, social life, and others just at their fingertips. Nowadays, world of mobile becomes wider with lot of users from children, teenagers, until elderly people. Unfortunately, mobile application is often developed to deliver business objectives, rather than by its usability from the perspectives of end user. This study aims to evaluate the mobile application in terms of its usability from the perspectives of children whom diagnose have Dyslexia. This aims achieved by performing the pre- and post-usability evaluation to see the comparison of usability level, and using satisfaction survey based on the five usability attributes defined by Nielsen quality model: learnability, efficiency, memorability, errors, and satisfaction. The result identifies that user’s suggestion and recommendation is important to developed the prototype and thus the usability level is increased in terms of all usability attributes.